Beyond mobility. Planning cities for people and places. - Cervero, Robert; Guerra, Erick; Al, Stefan (Island Press, 2017)
The authors draw on experiences and data from a range of cities and countries around the globe in making the case for moving beyond mobility. Throughout the book, they provide an optimistic outlook about the potential to transform places for the better. The book celebrates the growing demand for a shift in global thinking around place and mobility in creating better communities, environments, and economies.
Keywords: Stadtentwicklung; Verkehrsplanung; Mobilität; Öffentlicher Verkehr; ÖPNV; Verkehrsraum; Nachhaltigkeit; Stadtverkehr; Transitverkehr; Stadtumland; Suburbaner Raum; Transformation; Straßenverkehr; Verkehrstechnologie